a) x - 8 = 3x + 4
= \(x-3x=4+8\)
= \(-2x=12\)
-> \(x=-6\)
b) | x | + 15 = 29
= | x | = 14
-> \(x=\left\{\begin{matrix}-14\\14\end{matrix}\right.\)
c) 17 - | x | = 6
= | x | = 11
-> x \(x\left\{\begin{matrix}-11\\11\end{matrix}\right.\)
a) x - 8= 3x +4
-8 -4 =3x - x
-12 = 2x
=> 2x = - 12
x = - 12 ; 2
x = - 6
b) \(\left|x\right|\) + 15 =29
\(\left|x\right|\) = 29 -15
\(\left|x\right|\) = 14
=> x = 14 hoặc x = - 14
Vậy : x = 14 hoặc x = `-14
c) 17 - \(\left|x\right|\) = 6
\(\left|x\right|\) = 17 -6
\(\left|x\right|\) = 11
=> x=11 hoặc x= -11
Vậy : x= 11 hoặc x = -11